2009
DOI: 10.1113/jphysiol.2009.177352
|View full text |Cite
|
Sign up to set email alerts
|

Muscle sympathetic nerve activity during intense lower body negative pressure to presyncope in humans

Abstract: Activation of sympathetic efferent traffic is essential to maintaining adequate arterial pressures during reductions of central blood volume. Sympathetic baroreflex gain may be reduced, and muscle sympathetic firing characteristics altered with head-up tilt just before presyncope in humans. Volume redistributions with lower body negative pressure (LBNP) are similar to those that occur during haemorrhage, but limited data exist describing arterial pressure-muscle sympathetic nerve activity (MSNA) relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
111
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(126 citation statements)
references
References 46 publications
14
111
1
Order By: Relevance
“…MCA diameter does not change with mild sympathetic activation induced by LBNP up to Ϫ40 mmHg (39), which may be comparable to our LT group, but not the HT group, as they reached levels of LBNP Ն 70 mmHg. During greater levels of LBNP, there is increased sympathetic nerve activity in the periphery (8), but it is unknown whether cerebral sympathetic activity also increases, which could constrict the cerebral vessels. If this did occur, however, CBF would be further decreased relative to the observed reduction in velocity (i.e., we would be underesti-mating the reduction in flow).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCA diameter does not change with mild sympathetic activation induced by LBNP up to Ϫ40 mmHg (39), which may be comparable to our LT group, but not the HT group, as they reached levels of LBNP Ն 70 mmHg. During greater levels of LBNP, there is increased sympathetic nerve activity in the periphery (8), but it is unknown whether cerebral sympathetic activity also increases, which could constrict the cerebral vessels. If this did occur, however, CBF would be further decreased relative to the observed reduction in velocity (i.e., we would be underesti-mating the reduction in flow).…”
Section: Discussionmentioning
confidence: 99%
“…Despite similar reductions in MCAv in both groups, however, there was an immediate and progressive decrease in ScO 2 in the LT group only from Ϫ15 mmHg LBNP (P ϭ 0.004, Cohen's dϭ1. 8), but no change in ScO 2 for the HT group at any level of LBNP up to Ϫ60 mmHg; ScO 2 only began to fall below baseline from Ϫ75 mmHg LBNP in HT subjects (P Ͻ 0.001, Data are expressed as means Ϯ SD for age, height, weight, and means Ϯ SE for all other data. HT, high tolerance; LT, low tolerance; LBNP, lower body negative pressure; HR, heart rate; MAP, mean arterial pressure.…”
Section: Lbnp Tolerancementioning
confidence: 99%
“…Vaddadi et al (8) demonstrated that efferent sympathetic activity was maintained during vasovagal syncope episodes, and they speculated that activation of vasodiIator mechanisms may be responsible for vasovagal syncope. In addition, Cooke et al (9) showed that withdrawal of muscle sympathetic activity is not mandatory for presyncope. Some studies have shown that without decrease in peripheral vascular resistance, decrease in cardiac output alone can cause presyncope (1,10).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the above hypothesis has been challenged by studies showing that sympathetic withdrawal was not a pre-requisite for syncope [8,14,38]. Indeed, more than 2 decades ago, VVS was reported in heart transplant recipients and more recently several investigators made the observation that decreases in cardiac output contributed to the hypotension independent of reflex-mediated changes [14,20,39].…”
Section: Pathophysiology Of Ttt Induced Syncopementioning
confidence: 99%